Kinetics of growth of spherical GP zones: experimental verification of the vacancy pump model - Ipohorsky, Miguel; Bonfiglioli, Alberto F. (Pergamon Press, 1970)
Fil: Ipohorsky, Miguel Comisión Nacional de Energía Atómica; Argentina